Leaves of Quercus ilex L. as biomonitors of PAHs in the air of Naples (Italy) - Alfani, Anna; Maisto, Giulia; Vittoria Prati, Maria; Baldantoni, Daniela (Atmospheric Environment, 2001)
Polycyclic aromatic hydrocarbons (PAHs)were determined by the GC-MS chromatography in the leaves of Quercus ilex L., an evergreen Mediterranean oak, to monitor the degree of pollution in the urban area of Naples compared to remote areas. Leaf samples were collected in July 1998 from four urban parks, six roadsides and two sites in remote areas. The total PAH contents in Q. ilex leaves ranged from 106.6 in a control site to 4607.5 ng/g d.w. along a road with a high tra$c #ow. The mean concentration factors (urban/control)were 3.8 for the parks and 15 for the roads. The contribution of carcinogenic PAHs (benz[a]anthracene, benzo[b]#uoranthene, benzo[k]#uoranthene, benzo[a]pyrene, dibenz[a,h]anthracene, indeno[1,2,3-c,d]pyrene)was higher in urban area and di!ered according to the site, ranging from 6.7% to 21.3%. The total PAH burden in control sites was dominated by the low molecular weight PAHs, whilst along the urban roads #uoranthene, pyrene and benz[a]anthracene among the measured PAHs showed the highest values. PAHs were positively correlated (P(0.01)to trace metals measured in a previous study.
Keywords: biomonitoring; leaves; polycyclic aromatic hydrocarbons; Quercus ilex L; rural and urban areas

Leaves of Quercus ilex L. as biomonitors of PAHs in the air of Naples (Italy) - Alfani, Anna; Maisto, Giulia; Vittoria Prati, Maria; Baldantoni, Daniela (Atmospheric Environment, 2001)
Polycyclic aromatic hydrocarbons (PAHs)were determined by the GC-MS chromatography in the leaves of Quercus ilex L., an evergreen Mediterranean oak, to monitor the degree of pollution in the urban area of Naples compared to remote areas. Leaf samples were collected in July 1998 from four urban parks, six roadsides and two sites in remote areas. The total PAH contents in Q. ilex leaves ranged from 106.6 in a control site to 4607.5 ng/g d.w. along a road with a high tra$c #ow. The mean concentration factors (urban/control)were 3.8 for the parks and 15 for the roads. The contribution of carcinogenic PAHs (benz[a]anthracene, benzo[b]#uoranthene, benzo[k]#uoranthene, benzo[a]pyrene, dibenz[a,h]anthracene, indeno[1,2,3-c,d]pyrene)was higher in urban area and di!ered according to the site, ranging from 6.7% to 21.3%. The total PAH burden in control sites was dominated by the low molecular weight PAHs, whilst along the urban roads #uoranthene, pyrene and benz[a]anthracene among the measured PAHs showed the highest values. PAHs were positively correlated (P(0.01)to trace metals measured in a previous study.
Keywords: biomonitoring; leaves; polycyclic aromatic hydrocarbons; Quercus ilex L; rural and urban areas

Leaf Contamination by Atmospheric Pollutants as Assessed by Elemental Analysis of Leaf Tissue, Leaf Surface Deposit and Soil - Alfani, Anna; Maisto, Giulia; Iovieno, Paola; Rutigliano, Flora a.; Bartoli, Giovanni (Journal of Plant Physiology, 1996)
In order to evaluate the influence of air pollutants influx on leaf elemental composition, the concentration ofN, S, Cu, Fe and Pb were analyzed in the surface deposit and tissue of Quercus ilex L. leaves from 8 sites of the urban area of Naples. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total contents of Nand S and for available contents ofCu, Fe and Pb. In the leafsurface deposit S content was high though significantly (P<O.OOl) lower than in the leaf tissue, whilst N was not detectable. Cu, Pb and Fe contents in leafsurface deposit were conspicuous. The Pb content was higher in the leafsurface deposit than in the leaf tissue. No correlation between leaftissue and surface deposit contents was found for S or for Fe. By contrast, positive and significant correlations (P < 0.01) were found between leaf deposit and leaf tissue for both Cu and Pb. Nand S contents in the leaves were not correlated to the respective contents in the soil and the same was also found for Cu and Fe. In contrast with the presence of limiting concentrations in the soil, N, S and Fe leaf contents were significantly higher than in the leaves from remote sites. The data suggest that direct uptake of airborne pollutants, in addition to root absorption, may influence leaf elemental composition of Q. ilex L. leaves.
Keywords: air pollution; leaf contamination; nitrogen; Quercus ilex L; sulphur; Trace metals

Leaf Contamination by Atmospheric Pollutants as Assessed by Elemental Analysis of Leaf Tissue, Leaf Surface Deposit and Soil - Alfani, Anna; Maisto, Giulia; Iovieno, Paola; Rutigliano, Flora a; Bartoli, Giovanni (Journal of Plant Physiology, 1996)
In order to evaluate the influence of air pollutants influx on leaf elemental composition, the concentration ofN, S, Cu, Fe and Pb were analyzed in the surface deposit and tissue of Quercus ilex L. leaves from 8 sites of the urban area of Naples. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total contents of Nand S and for available contents ofCu, Fe and Pb. In the leafsurface deposit S content was high though significantly (P<O.OOl) lower than in the leaf tissue, whilst N was not detectable. Cu, Pb and Fe contents in leafsurface deposit were conspicuous. The Pb content was higher in the leafsurface deposit than in the leaf tissue. No correlation between leaftissue and surface deposit contents was found for S or for Fe. By contrast, positive and significant correlations (P < 0.01) were found between leaf deposit and leaf tissue for both Cu and Pb. Nand S contents in the leaves were not correlated to the respective contents in the soil and the same was also found for Cu and Fe. In contrast with the presence of limiting concentrations in the soil, N, S and Fe leaf contents were significantly higher than in the leaves from remote sites. The data suggest that direct uptake of airborne pollutants, in addition to root absorption, may influence leaf elemental composition of Q. ilex L. leaves.
The following values have no corresponding Zotero field: publisher: Gustav Fischer Verlag, Stuttgart
Keywords: air pollution; leaf contamination; nitrogen; Quercus ilex L; sulphur; Trace metals